CHEMICAL COMPOSITION OF ROOT CHICORY - O. M. Vyutnova; I. A. Novikova (Овощи России, 2019)
The value of the root chicory is due to the unique chemical composition of its roots. Depending on the variety, place of growth and growing conditions of culture chicory roots contain 72.0-77.0% water, 1.0-1.2% protein, 0.1-0.3% fat, 1.0-6.0% sugar, 12.0-30% inulin, 1.3-1.8% fiber, 1.1-1.9% ash, 0.3-0.4% phosphorus, 1.3-1.4% potassium, 0.3-0.4% calcium. Chicory roots can serve as a raw material for the production of various products: coffee surrogate, alcohol, sugar substitute and inulin in its pure form. Depending on the type of final product, the processing industry has different requirements for the chemical composition of the root crops. Coffee-chicory industry makes demands of the high content of inulin in the roots as the main nutritional flavor substratum, the high content of glucoside of inhibin reporting chicory drink a specific coffee flavor and aroma, and low content of proteins. The sugar industry is interested in a high percentage of inulin and other soluble carbohydrates that are easily converted into sugars, and in a small content of intibin, which gives the product a bitter taste, as well as in a small amount of proteins that are the most malicious pathogens that complicate sugar extraction. In the production of pure inulin, the processing industry is primarily interested in ensuring that the content of this carbohydrate in the root crops is as high as possible. The alcohol industry is interested in a high content of soluble carbohydrates as the main source material for alcohol, in a high content of soluble proteins as a nutrient substrate for the development of yeast cultures in the fermentation of sugar and in a high content of phosphorus and potassium salts, also necessary for the successful reproduction of yeast. The article reflects the economic importance of root chicory as a raw material for the needs of different types of industry (coffee-cyclical, alcohol, sugar), depending on the content of different substances in the root crops. The chemical composition, dynamics of accumulation of substances during the growing season and their distribution in different parts of the root crop are reflected.